Assessment of Heavy Metals in Surface and Ground Water Sources under Different Land Uses in Mid-hills of Himachal Pradesh - Rana, Anchal; Bhardwaj, S. K; Thakur, M.; Verma, Sudhir (International Journal of Bio-resource and Stress Management, 2023)
Investigations were carried out on analysis of water samples for heavy metals viz. Arsenic, Cadmium, Iron, lead, and zinc from surface and ground water from 12 sampling sites under agriculture, forest and urban land use during rainy, winter and summers seasons in areas was adjoining to Solan block of district Solan of Himachal Pradesh, India. The study carried during 2011−2012 in order to elucidate the fate of heavy metals in surface and ground water. The maximum As (0.05 ppb), Cd (0.14 ppb), Fe (1.68 ppb) and Pb (0.14 ppb) of surface water was recorded under urban land use system whereas Zn (0.46 ppb) was observed in forest land use. Maximum As (0.05 ppb), Fe (1.52 ppb), Pb (0.17 ppb) and Zn (0.59 ppb) of surface water was recorded during rainy seasons, whereas Cd (0.11 ppb) was recorded during summer seasons. In ground water, maximum As (0.03 ppb), Fe (2.83 ppb) and Zn (0.73 ppb) was noticed under forest land use system, whereas, Cd (0.18 ppb) in urban land use system and Pb (0.13 ppb) was recorded under agriculture land use system. Maximum As (0.04 ppb), Zn (0.98 ppb) and Pb (0.22 ppb) of ground water were recorded during rainy season, whereas, Cd (0.20 ppb) was recorded in summer season and Fe (2.74 ppb) in winter season. Hence, the study indicated that the common land uses in the mid-hills of Solan district did not influence the surface and ground water quality adversely.